Implementasi Pembelajaran Berdiferensiasi Ilmu Pengetahuan Alam dan Sosial Kelas IV Sekolah Dasar Negeri Galeh 1 Kecamatan Tangen Kabupaten Sragen Tahun Pelajaran 2024/2025 - Dewi Nuranisa Putri; Dwi Anggraeni Siwi (JURNAL RISET RUMPUN ILMU PENDIDIKAN, 2025)
This study aims to describe and explain the challenges and obstacles in implementing differentiated learning in Science and Social Studies (IPAS) for fourth-grade students at Galeh 1 Public Elementary School, Tangen District, Sragen Regency, in the  2024/2025 academic year. The research employed a qualitative descriptive method, with the study conducted at Galeh 01 Elementary School in April 2025. The research subjects included the fourth-grade teacher and students, consisting of 8 male and 11 female students. Data collection techniques involved observation, interviews, and documentation, analyzed using the interactive data analysis model by Miles & Huberman. The results of the study show that: a) content differentiation was evident through the teacher's systematic preparation of IPAS teaching modules, provision of learning materials, and the use of PowerPoint and concrete images as media; b) process differentiation was demonstrated through varied assignments in group and individual formats, tailored approaches according to academic levels, and the use of an LCD projector to support learning; c) product differentiation was observed through students being given opportunities to present and the teacher providing summative assessments as a measure of understanding; d) the learning environment element was reflected in the teacher creating a fun and conducive classroom atmosphere. 2) The challenges and obstacles in implementing differentiated learning included: a) the presence of passive students, b) limited facilities and infrastructure, c) the time-consuming process of preparing learning components, and d) student dependency on peers.